Likuiditas Memediasi Pengaruh Ukuran Perusahaan Dan Risiko Bisnis Terhadap Profitabilitas Perusahaan Perbankan Yang Terdaftar Di BEI - Ni Wayan Yessi Agustian; Ni Wayan Suartini; I Nyoman Gede Supraptha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research was conducted to determine the role of liquidity in mediating the influence of company size and business risk on the profitability of banking companies listed on the Indonesia Stock Exchange (BEI). The population in this study was 57 companies in the banking sub-sector listed on the Indonesian Stock Exchange. Based on the predetermined criteria, 32 banking companies were obtained, so that the research sample studied amounted to 96 sample data. In this research, the data analysis technique used is the path analysis technique with the help of the Smart-PLS 4 application. The research results show that partially the variable Size, NPL, and LDR do not have a significant effect on ROA, while the BOPO variable has a significant effect on ROA. Size does not have a significant effect on ROA through LDR as a mediating variable. NPL does not have a significant effect on ROA through LDR as a mediating variable. BOPO does not have a significant effect on ROA through LDR as a mediating varia.